Book Review: Trihartono, A., & Putri, E. A. L. (2025). Diplomasi Gelombang Korea (Hallyu): Aktor, Media, dan Dampak. KHD Production. 187 pp. - Nissa Nurhaliza; Muhammad Irvan Wibowo (Universitas Wijaya Kusuma Surabaya, 2026)
This article reviews Diplomasi Gelombang Korea (Hallyu): Aktor, Media, dan Dampak, analyzing Hallyu as a strategic soft power instrument. The book systematically maps the ecosystem from historical roots to the digital 3.0 era, highlighting the synergy between state and private actors. While offering a comprehensive chronological narrative, this review interrogates its state-centric framework. By integrating “success without design” and non-state agency perspectives, the article challenges the portrayal of the government as an omnipotent architect. Furthermore, it explores the evolving role of fandoms as independent referees and the causal link between exploitative business models and Hallyu’s global competitiveness. Ultimately, it emphasizes the need for a more nuanced understanding of ethical contradictions within contemporary cultural diplomacy.